PELATIHAN GURU PAI DALAM PENGEMBANGAN BAHAN AJAR PADA MURID DI SD NEGERI RENGASDENGKLOK SELATAN 2 - Aas Agustini (SABA JAYA PUBLISHER, 2023)
This study discusses Learning Training and Islamic Education Teacher Strategies in Developing Teaching Materials for Students at SDN Rengasdengklok Selatan 2. The type of research used is qualitative research. The research approach uses interdisciplinarity, including: management, pedagogical, sociological, and psychological approaches. The primary data source of this study is the teacher of Islamic Religious Education. Secondary data sources in this study were school profile data, theories about the concept of teaching material development strategies, the concept of teacher strategies in the learning process, and teaching material development theory. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use the stages of data reduction, data presentation, and withdrawal. Conclusion. The results of the study found that the learning strategies of Islamic Religious Education in the Formation of the Muslim personality of students used two learning strategies, namely direct learning and indirect learning.